Successful Regenerative Endodontic Procedure of a Nonvital Immature Permanent Central Incisor Using Amniotic Membrane as a Novel Scaffold - Nandini Suresh; Buvaneshwari Arul; Dinesh Kowsky; Velmurugan Natanasabapathy (MDPI AG, 2018)
Successful regenerative endodontic procedure was performed in nonvital immature permanent central incisor (Stage-4 root development) using human amniotic membrane (HAM) as a novel scaffold. The treatment was performed according to the American Association of Endodontics guidelines with minimal canal instrumentation, 1% Sodium hypochlorite as irrigant and calcium hydroxide as intracanal medicament. During the second appointment, HAM was placed as a scaffold and Biodentine™ was layered over the HAM with glass ionomer cement and resin composite as coronal seal. Preoperative and post-operative cone beam computed tomography (at three years) was taken to assess the treatment outcome. The resolution of disease process and increase in canal width, as well as positive response to pulp sensitivity tests, were observed by the end of three years. There was approximately 78–86% reduction in the volume of periapical lesion size. This case report confirms that HAM can be used as a scaffold material for successful regenerative endodontic procedure (REP).